Research progress in rechargeable magnesium-sulfur secondary batteries - DU Wentao; YAN Xiaoyan; LIU Baosheng; ZHAO Xinxin; ZHANG Xiaohua; WANG Mingju (Cailiao gongcheng)
Emerging energy storage technologies must meet the requirements of low cost， reasonable safety， rich natural resources and high energy density. The rechargeable magnesium sulfur （Mg-S） battery has the advantages of high energy density， high safety， low cost，and so on. However， its performance is limited by self-discharge， rapid capacity loss， magnesium anode passivation，and low sulfur utilization. The recent advances in Mg-S battery research， focusing on the advances in non-nucleophilic electrolytes， anodes，and cathodes， summarizing electrolytes that can facilitate reversible deposition and dissolution of magnesium ions，and maintaining compatibility with sulfur cathodes and other battery components are reviewed in this paper. In addition， the current challenges of magnesium-sulfur batteries are discussed in the context of research trends， such as the dissolution and diffusion of sulfides and the slow reaction kinetics of Mg-S batteries， as well as recommendations for the future， such as doping MOFs with different elements and exploring the reaction mechanism of the batteries.